Pengaruh Kemampuan Manajerial dan Kreativitas Guru PAI Terhadap Prestasi Belajar Siswa SMA Wahid Hasyim Pati - Puspitasari, Meliya; Surachman, Anista Ika (AL-BURHAN, 2023)
The purpose of this study was to determine the Influence of Managerial Ability and Teacher Creativity on Student Achievement at SMA Wahid Hasyim Pati. This study is included in the type of correlation research using a quantitative approach. The study was conducted in February - August 2022 with a population of active students, namely 28 class X students and 43 class XI students, the sampling technique used a saturated sampling technique. The independent variables are managerial ability (X1) and teacher creativity (X2) with the dependent variable being the learning achievement of Islamic Religious Education students (Y). The data collection method used a questionnaire, and documentation and the data analysis technique used multiple linear regression analysis. The results of the study showed a positive and significant influence between managerial ability and creativity on student achievement at SMA Wahid Hasyim Pati. This is evidenced by testing at a 5% error level, Freg was obtained at 6.621 which is greater than Ftable = 3.13. (6.621 3.13)Keywords: managerial ability, teacher creativity, learning achievement